2017
DOI: 10.1111/eip.12408
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from child and adolescent mental health services with attention‐deficit hyperactivity disorder in Ireland: Case note review

Abstract: KeywordsAttention-deficit hyperactivity disorder, ADHD, transition, child and adolescent mental health services, adult mental health services, CAMHS, AMHS ADHD transitions case note review Ireland Abstract AimIn a context of international concern about early adult mental health service provision, this study identifies characteristics and service outcomes of young people with attention-deficit hyperactivity disorder (ADHD) reaching the child and adolescent mental health service (CAMHS) transition boundary in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 44 publications
(96 reference statements)
0
49
1
Order By: Relevance
“… 3 A study from the Republic of Ireland used the same methodology and found 20 ADHD cases from 4 CAMHS teams annually requiring transition, with only 3 individuals successfully transitioning to an adult service. 4 Similarly there are a lack of comparative international data on transition in ADHD; an ongoing European study on transition focuses on mental health transition generally but is not specific to ADHD. 14 Given the rise in prescriptions for ADHD over the past decades, 15 estimates may quickly become out of date as later cohorts are likely to contain a higher proportion of young adults who may have benefitted from medication and therefore wish to continue to take it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 A study from the Republic of Ireland used the same methodology and found 20 ADHD cases from 4 CAMHS teams annually requiring transition, with only 3 individuals successfully transitioning to an adult service. 4 Similarly there are a lack of comparative international data on transition in ADHD; an ongoing European study on transition focuses on mental health transition generally but is not specific to ADHD. 14 Given the rise in prescriptions for ADHD over the past decades, 15 estimates may quickly become out of date as later cohorts are likely to contain a higher proportion of young adults who may have benefitted from medication and therefore wish to continue to take it.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to quantify national estimates for transition, but they have either focused on all neurodevelopmental conditions rather than just ADHD or were limited geographically. 3 , 4 …”
mentioning
confidence: 99%
“…Others have argued that transition planning should incorporate a developmental perspective (Singh, Anderson, Liabo, & Ganeshamoorthy, 2016) which may be particularly important for young people with ADHD, who by definition have poor executive functioning and selfmanagement (Fogler et al, 2017); the recommendations from the expert policy paper (Asherson et al, 2017) also emphasise that the transition should be planned as developmentally appropriate for the patient which is not mentioned by NICE. The transition to an adult service also often occurs at a critical time when young people are also encountering changes in education, employment and independence from parents (Tatlow-Golden et al, 2017). Boilson et al (2013) suggests that information regarding the patient's employment, social circumstances and quality of life is important to support effective transition, which is highlighted in the general NICE guidance (NG43), but overlooked in the more specific recommendations for ADHD (NG87).…”
Section: Discussionmentioning
confidence: 99%
“…If those who partially meet the full criteria, or are considered to be in partial remission, are included this figure rises to 65% at 25 years (Faraone, Biederman, & Mick, ). This has led to the increasing recognition that ADHD is a life span disorder (Tatlow‐Golden et al., ) which raises the issue of transition from child to adult services. Several studies, government documents and policy guidelines highlight the difficulty for young people who require a transition between children's services (usually Child and Adolescent Mental Health Services (CAMHS) or Paediatrics) and adult services (Singh, Paul, Ford, Kramer, & Weaver, ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking an approach that plans for the cessation of services or young people's disengagement from services may result in better outcomes than unplanned disengagement. 23 CAMHS services should consider teaching young people to recognise their own symptoms and impairments, and triggers for crises, to manage their mental health, and to participate in shared decision-making; this may improve outcomes following a gap or cessation of CAMHS/AMHS input. This may be especially important for those young people identified as at risk of disengagement.…”
Section: Identifying Those Most At Risk Of Negative Outcomesmentioning
confidence: 99%